2017
DOI: 10.1097/bpo.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

A Graphic Overlay Method for Selection of Osteotomy Site in Chronic Radial Head Dislocation: An Evaluation of 3D-printed Bone Models

Abstract: Level IV-therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Some researchers believed that center of rotation angulation (CORA) might be a better site for osteotomy, while others recommended meta-to-diaphyseal area. [ 28 - 30 ] Recent studies have shown that the involvement of proximal radioulnar joint (PRUJ) should not be ignored in chronic Monteggia fracture, as it can be an important factor for prognosis. [ 3 , 8 ] In this study, we chose a plane where would be a possible proximal border of a radial notch, as we considered that the interaction between the radial tubercle and the callus during postoperative physical rehabilitation would bring out a notch-like callus for PRUJ reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believed that center of rotation angulation (CORA) might be a better site for osteotomy, while others recommended meta-to-diaphyseal area. [ 28 - 30 ] Recent studies have shown that the involvement of proximal radioulnar joint (PRUJ) should not be ignored in chronic Monteggia fracture, as it can be an important factor for prognosis. [ 3 , 8 ] In this study, we chose a plane where would be a possible proximal border of a radial notch, as we considered that the interaction between the radial tubercle and the callus during postoperative physical rehabilitation would bring out a notch-like callus for PRUJ reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures that address congenital deformities can also benefit from preoperative 3D models. These models also have wide application in orthopaedic and faciomaxillary practice to address complex malunions, plan relevant osteotomies and correct deformities that require extensive, multiplanar reconstructions. Intraoperative use of bespoke drills and resection guides used in osteotomies can allow depth and angle control, as seen in many successful mandibular reconstructions.…”
mentioning
confidence: 99%